Shape coexistence: the shell model view. (14th January 2016) - Poves, A
Abstract: We shall discuss the meaning of the 'nuclear shape' in the laboratory frame proper to the spherical shell model. A brief historical promenade will bring us from Elliott's SU3 breakthrough to today's large scale shell model calculations. A section is devoted to the algebraic model which extends drastically the field of applicability of Elliot's SU3, providing a precious heuristic guidance for the exploration of collectivity in the nuclear chart. Shape coexistence and shape mixing will be shown to occur as the result of the competition between the main actors in the nuclear dynamics; the spherical mean field, and the pairing and quadrupole–quadrupole interactions. These ideas will be illustrated with examples in magic nuclei ( 40 Ca and 68 Ni); neutron rich semi-magic ( 32 Mg, and 64 Cr); and in proton rich N = Z ( 72 Kr).